Uterine EMG Signals Spectral Analysis for Pre-Term Birth Prediction - Tsipouras, M. G. (Engineering, Technology & Applied Science Research, 2018)
A methodology for prediction of pre-term births is presented in this paper. The methodology is based on the analysis of EHG signals and data mining techniques. Initially, spectral and non-linear characteristics of the EHG are extracted, forming a pattern that is used to train a classifier to discriminate between term and pre-term cases. The method has been tested using a benchmark EHG database, and the obtained results indicate its effectiveness in accurate pre-term/term labour prediction.